Goal attainment among veterans with PTSD enrolled in peer-delivered whole health coaching: a multiple baseline design trial. Issue 2 (3rd July 2022) - Johnson, Emily M.; Possemato, Kyle; Martens, Brian K.; Hampton, Brittany; Wade, Michael; Chinman, Matthew; Maisto, Stephen A.
ABSTRACT: The objective was to estimate the efficacy of peer-delivered Whole Health Coaching with individual veterans with PTSD in primary care. This study examined changes in goal attainment before, during, and after peer-delivered Whole Health Coaching using a concurrent multiple-baseline design across participants with replication across cohorts. Ten primary care veterans with symptoms of PTSD were included. The primary outcome, goal attainment, was analysed using multilevel modelling, non-overlap of all pairs (NAP) effect size, and visual inspection. Across all three analyses, peer-delivered Whole Health Coaching was associated with increased and sustained goal attainment in some Veterans with PTSD. Multilevel modelling demonstrated that at the sample level, goal attainment was significantly higher during peer-delivered Whole Health Coaching, t  = 2.49, p  < .05. Multilevel modelling revealed significant improvement for 4 of 10 participants; NAP and visual inspection demonstrated moderate to large effects for 6 of 10 participants. Peer-delivered Whole Health Coaching may help veterans with PTSD make progress on individualised goals. Future research should replicate these findings and evaluate which participants may be most likely to benefit.